Literatura afro-brasileira e a descolonização de identidades negras no romance Rio Negro, 50 de Nei Lopes - Carvalho, Consoelo Costa Soares (2021)
Afro-Brazilian Literature conceived as a strand of Brazilian Literature has as its basis to reframe the ways of representation of the black, constituting the black presence beyond the object. Thus, the objective of this study is to demonstrate that Afro-Brazilian Literature promotes the construction of black identities in the national literary field. For this purpose, the novel Rio Negro, 50 (2015), authored by Nei Lopes, is analyzed. The hypothesis is that the characters of this novel, each in their own way, seek to subvert the violence arising from racism and its tentacles in a gesture of decolonization of black identities. The analysis promoted a discussion on the concept of Afro-Brazilian Literature, on the decolonization of black identity, and on the questioning of control images attributed to blacks. Such reflections showed that the existence of a literary segment supported by black identity in a society whose coloniality of knowledge and power remain, in addition to promoting the construction of black identities in the national literary fabric, returns to blacks the humanity previously forbidden by objectified representations. Such an understanding was possible because in this literary conjuncture the black person is no longer an object and becomes a subject. Subject of saying and saying without the intervention of a self that claims to be superior. The theoretical basis of this study transits between post-colonial, decolonial and feminist criticisms in dialogue with the studies of Brazilian ethnic-racial relations because they present an epistemic diversity that are complemented allowing the widening of the look for a better understanding of the object.